Interventions by healthcare professionals to improve management of physical long-term conditions in adults who are homeless: a systematic review protocol. Issue 8 (21st August 2017) - Hanlon, Peter; Yeoman, Lynsey; Esiovwa, Regina; Gibson, Lauren; Williamson, Andrea E; Mair, Frances S; Lowrie, Richard
Abstract : Introduction: People experiencing homelessness are at increased risk of, and have poorer outcomes from, a range of physical long-term conditions (LTCs). It is increasingly recognised that interventions targeting people who are homeless should be tailored to the specific needs of this population. This systematic review aims to identify, describe and appraise trials of interventions that aim to manage physical LTCs in homeless adults and are delivered by healthcare professionals. Methods and analysis: Seven electronic databases (Medline, EMBASE, Cochrane Central Register of Controlled Trials, Assia, Scopus, PsycINFO and CINAHL) will be searched from 1960 (or inception) to October 2016 and supplemented by forward citation searching, handsearching of reference lists and searching grey literature. Two reviewers will independently review titles, abstract and full-texts using DistillerSR software. Inclusion criteria include (1) homeless adults with any physical LTC, (2) interventions delivered by a healthcare professional (any professional trained to provide any form of healthcare, but excluding social workers and professionals without health-related training), (3) comparison with usual care or an alternative intervention, (4) report outcomes such as healthcare usage, physical and psychological health or well-being or cost-effectiveness, (5) randomised controlled trials, non-randomised controlled trials, controlled before-after studies. Quality will be assessed using the Cochrane EPOC Risk of Bias Tool. A meta-analysis will be performed if sufficient data are identified; however, we anticipate a narrative synthesis will be performed. Ethics and dissemination: This review will synthesise existing evidence for interventions delivered by healthcare professionals to manage physical LTCs in adults who are homeless. The findings will inform the development of future interventions and research aiming to improve the management of LTCs for people experiencing homelessness. Ethical approval will not be required for this systematic review as it does not contain individual patient data. We will disseminate the results of this systematic review via conference presentations, healthcare professional networks, social media and peer-reviewed publication. Trial registration number: PROSPERO registration number: CRD42016046183.